A 3D phenomenological yield function with both in and out-of-plane mechanical anisotropy using full-field crystal plasticity spectral method for modelling sheet metal forming of strong textured aluminum alloy. (1st June 2020) - Liu, Wencheng; Chen, Bernard K.; Pang, Yong; Najafzadeh, Ali
Abstract: In this paper, a multi-scale model for AA3104-H19 and AA2024-T3 aluminium alloy with strong cold rolled crystallographic texture is proposed. This model consists of two components: (i) a full-field crystal plasticity spectral method using fast Fourier transformation (CPFFT) that can be used to predict anisotropic mechanical properties in both the in and out-of-plane uniaxial and multi-axial stress states and (ii) a 3D new phenomenological anisotropic yield function with enough flexibility to describe the in and out-of-plane mechanical anisotropies of strongly textured aluminium alloy sheet. This multi-scale model was implemented into a commercial finite element (FE) software Abaqus via a user-defined material subroutine UMAT to predict the anisotropic plastic deformation in a multi-step forming process (deep drawing). Results showed that this new modelling approach is able to accurately predict earing profiles with multiple ears in deep drawn cups based on the crystallographic texture information data obtained from orientation density functions (ODFs).